Disparities in Diabetes Management in Asian Americans in New York City Compared With Other Racial/Ethnic Minority Groups - Islam, Nadia S. (Am J Public Health, 2015)
We examined diabetes management practices among Hispanics, Blacks, and 3 Asian American subgroups in New York City. Compared with Blacks and Hispanics, all 3 Asian American subgroups had lower average rates of diabetes management practices. Compared with Blacks, Chinese and Koreans were significantly less likely to participate in all diabetes management behaviors and practices, whereas Asian Indians were significantly less likely to perform feet checks or undergo an eye examination. Results demonstrated the need for health care provider interventions and training to support diabetes management among Asian Americans.